2017
DOI: 10.1002/dmrr.2885
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of basal‐bolus insulin regimens in the inpatient management of non‐critically ill patients with type 2 diabetes: A systematic review and meta‐analysis

Abstract: Hyperglycemia during hospitalization is associated with increased rates of complications and longer hospital stays. Various insulin regimens are used in the inpatient diabetes management of non-critically ill patients. In this systematic review and meta-analysis, we aimed to assess the efficacy and safety of basal-bolus insulin therapy (BBI) by summarizing evidence from studies of BBI versus sliding scale insulin therapy (SSI) in the management of hospitalized non-critically ill type 2 diabetes patients. We se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 27 publications
1
24
2
2
Order By: Relevance
“…Conventional insulin therapy is less responsive to alterations in insulin requirements, and despite frequent blood glucose monitoring and regular adjustment of insulin doses, tighter glycaemic control with conventional therapy is associated with increased risk of hypoglycaemia and related adverse medical outcomes. [15][16][17] Our study shows that overnight insulin requirements were higher in patients receiving nutritional support than in previous closed-loop inpatient studies, 8,11 probably due to the timing and duration of the feed compared with patients with standard oral intake. This increased insulin requirement coupled with fear among health-care professionals of hypoglycaemia and associated adverse outcomes-especially overnight-might contribute to the prevalent hyperglycaemia in the control group.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Conventional insulin therapy is less responsive to alterations in insulin requirements, and despite frequent blood glucose monitoring and regular adjustment of insulin doses, tighter glycaemic control with conventional therapy is associated with increased risk of hypoglycaemia and related adverse medical outcomes. [15][16][17] Our study shows that overnight insulin requirements were higher in patients receiving nutritional support than in previous closed-loop inpatient studies, 8,11 probably due to the timing and duration of the feed compared with patients with standard oral intake. This increased insulin requirement coupled with fear among health-care professionals of hypoglycaemia and associated adverse outcomes-especially overnight-might contribute to the prevalent hyperglycaemia in the control group.…”
Section: Discussionmentioning
confidence: 54%
“…The mean Charlson Comorbidity Index score was higher in the closed-loop group than in the control group (appendix). Total hospital stay was longer in the control group (median 32 days [IQR 25-47]) than in the closedloop group (18 days [14-26]; p=0•013); however, length of hospital stay from study enrolment to discharge was similar between groups (15 days in the control group vs 10 days [6][7][8][9][10][11][12][13][14][15][16][17][18][19] in the closed-loop group; p=0•13).…”
Section: Resultsmentioning
confidence: 99%
“…Different trials have been conducted to identify the best therapies for the hospital setting, and different basal-bolus regimens or basal-oral therapies have been compared to SSI [ 8 13 ]. A recent meta-analysis [ 21 ] showed that a significantly lower mean daily BG was achieved with basal-bolus schemes than with SSI, with no difference in the risk of severe hypoglycemia or in mean length of stay, but an increased risk of mild hypoglycemia. The increased risk of mild hypoglycemia can be explained by a pool of factors, such as fasting conditions before laboratory tests, lack of appetite due to disease, and short-acting and basal insulin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest considering basal insulin with correction scale instead of correction scale only; this is based on the ADA recommendations and multiple studies that were included in a meta-analysis. 5,8 Prandial insulin should be considered if needed to treat postprandial hyperglycemia. For correction scale insulin, we suggest using an approach included in Table 2, but other approaches are available and may be used.…”
Section: Inpatient Diabetes and Hyperglycemiamentioning
confidence: 99%